1999
DOI: 10.1046/j.1365-2591.1999.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue responses to calcium hydroxide‐based root canal medicaments

Abstract: All calcium hydroxide formulations caused an inflammatory response. The severity and longevity of the responses varied between pastes as a result of the various antiseptic agents. Although irritating, repair was apparent with all formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 14 publications
1
20
0
11
Order By: Relevance
“…Previous studies have reported that calcium hydroxide induces a lesser degree of inflammatory infiltrate in the initial hours, progressing to a moderate degree after longer periods, and inducing subsequent tissue repair. 20 The necrosis seen in pulp tissue following contact with calcium hydroxide is the result of its alkalinity. This alkalinity actually has a beneficial effect on the injured tissue, insofar as it causes mild irritation and stimulates the conjunctive tissue to defend and repair itself, initiating an inflammatory reaction to control and eliminate the irritating agent.…”
mentioning
confidence: 99%
“…Previous studies have reported that calcium hydroxide induces a lesser degree of inflammatory infiltrate in the initial hours, progressing to a moderate degree after longer periods, and inducing subsequent tissue repair. 20 The necrosis seen in pulp tissue following contact with calcium hydroxide is the result of its alkalinity. This alkalinity actually has a beneficial effect on the injured tissue, insofar as it causes mild irritation and stimulates the conjunctive tissue to defend and repair itself, initiating an inflammatory reaction to control and eliminate the irritating agent.…”
mentioning
confidence: 99%
“…In addition, it presents pH around 12.4 (9), high antibacterial activity (8), and biocompatibility (9,10).…”
mentioning
confidence: 99%
“…This may be due to responses to initial irritation in short periods when in touch with the tested material, or due to the surgical procedure [23]. Different results were observed by Nelson Filho et al [24], who reported that calcium hydroxide induces less inflammatory infiltrate in the initial hours, progressing to a moderate degree after longer periods, and inducing subsequent tissue repair.…”
Section: Discussionmentioning
confidence: 99%